PENGARUH TERPAAN IKLAN APLIKASI BIBIT DI PLATFORM YOUTUBE TERHADAP MINAT INVESTASI MAHASISWA DI KOTA DENPASAR - dewi, Aulia Anggradita; Suryawati, I Gusti Agung Alit; Gelgel, Ni Made Ras Amanda (E-Jurnal Medium, 2023)
Various sectors have developed into the digitalization era, and one of the things in the economy is investment or investment. One of the investment instruments is mutual funds, mutual funds are referred to as the investment instruments of choice for novice investors. One of the mutual fund investment provider applications is Investment Bibit. Various methods are used to increase the number of investors using the Bibit Investment application. one of which is to improve marketing communications by displaying advertisements regarding the Bibit Investment application through various social media. The Bibit application is one of the most downloaded applications by the millennial generation, this is due to the Bibit application being more suitable for novice investors and having features that are easier to understand. Several factors influence someone to use the Bibit application, namely service features. Investment applications that are equipped with service features can facilitate investors. With the appearance of advertisements for the Bibit application through the Youtube Platform and becoming the number one investment application in Indonesia, it is hoped that it will provide information regarding ease of investment in the Bibit investment application and attract students' interest in investing. The purpose of this study was to determine the effect of ad exposure to the Investment Bibit application on interest in investing in student mutual funds in the city of Denpasar. The research method uses quantitative descriptive analysis with data collection, namely distributing questionnaires to respondents. The number of samples used in this study amounted to 80 respondents. The data analysis technique used was inferential statistical analysis, namely a simple linear regression test. The results show that exposure to Investment Bibit advertisements through the Youtube platform has a positive effect on mutual fund investment interest among students in Denpasar City, where the value of the t-test is 8.108 with a p-value of 0.00 (<0.05). The emotional indicators show that respondents have a desire to continue investing and feel happy and satisfied when carrying out investment activities. In addition to the encouragement indikator where the respondent has a desire to find out about investment. Keywords: Investment Bibiti, Ad Exposure, Investment Interest.